2023
DOI: 10.1021/acssuschemeng.2c07388
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Polymer Functionalized Copper Nanocluster-Based Fluorescent Probe for the Selective and Sensitive Detection of S2– Ions

Abstract: The sensitive and selective detection of sulfide (S2–) ions in water is of major interest due to its toxicity and physiological effects on organisms. Herein, we have designed a fluorescent probe, poly(allylamine) hydrochloride (PAH) functionalized copper nanocluster (Cu NC@PAH), for the detection of S2– ions. The synthesis of the probe is based on the electrostatic interaction between negatively charged Cu NCs and the positively charged polymer, PAH. The drastic enhancement of the photoluminescence (PL) intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 65 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…In the case of Zn-induced aggregates of Au NCs, we observed an increase in average lifetime to 0.70 μs (Table ). The microsecond lifetime indicates the LMCT or LMMCT process involving excited electron relaxation through the triplet state. , In both systems, the photoexcited electrons on the S n state relaxed from the singlet state S 1 to triplet state T 1 through the ISC process and then relaxed to the ground state (Figure B). In the case of Zn 2+ -induced Au NCs, the Zn 2+ electrostatic interactions with the carboxylate ion of Au NCs restrict the rotation and vibration of ligands surrounding the cluster .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Zn-induced aggregates of Au NCs, we observed an increase in average lifetime to 0.70 μs (Table ). The microsecond lifetime indicates the LMCT or LMMCT process involving excited electron relaxation through the triplet state. , In both systems, the photoexcited electrons on the S n state relaxed from the singlet state S 1 to triplet state T 1 through the ISC process and then relaxed to the ground state (Figure B). In the case of Zn 2+ -induced Au NCs, the Zn 2+ electrostatic interactions with the carboxylate ion of Au NCs restrict the rotation and vibration of ligands surrounding the cluster .…”
Section: Resultsmentioning
confidence: 99%
“…Ligand-protected metal nanoclusters (MNCs) with less number of metal atoms having core diameters <2 nm are recognized as a new class of materials for their unique physicochemical properties, which are widely different from single metal atoms and larger-sized metal nanoparticles. These metal NCs exhibit many interesting properties including discrete HOMO–LUMO band gap, tunable photoluminescence (PL), large Stokes shift, and core–shell-type structures. , PL is one of the most fascinating properties of NCs, making them a promising candidate for various applications in bioimaging, sensing, and light harvesting. Different kinds of ligands have been used in the past few years for nanocluster synthesis such as proteins, peptides, DNA, and small thiol molecules. However, the weak luminescence of most of the metal NCs compared to the conventional fluorophore and colloidal QDs has severely limited their use in many photonic applications. Ligands have played an important role in the PL properties by (i) a ligand–core interaction, (ii) a ligand–solvent interaction like solvent polarity and pH, and (iii) other interactions like ligand-coordination complex formation, metallophilic interaction, and many more. Various synthesis and post-synthesis strategies have been employed to improve the PL intensity of metal NCs. The tailoring of size, doping, structure, surface modification, and AIE are efficient methods to enhance the PL intensity of weakly luminescent metal NCs. ,,, It is reported that the PL of metal clusters originates from the core of the NCs and the surface organic ligand shell .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] As a result, significant attention has been directed towards creating highly precise architectures and employing ligandprotected metal nanoclusters with atomic-level precision. [30][31][32] Metal NCs, due to their ultrasmall small sizes of nearly 2 nm with fascinating properties and atomic precision, have gained significant attention towards their applications in catalysis. [33][34][35][36] Atomically precise gold nanoclusters offer precise control over their geometric structure, electronic properties, and surface ligands, thus holding significant appeal as catalysts for electrochemical reactions due to their ultrasmall size and high surface-active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Natural enzymes are mainly composed of proteins and modulate biological reactions through substrate specificity and high catalytic activity under mild conditions. Various natural enzymes such as peroxidase, oxidase, catalase, ascorbic acid oxidase (AAO), etc. assist their specific substrates and convert them into products by generating reactive oxygen species (ROS). , Recently, research on nanomaterial-based artificial enzymes (nanoenzymes or nanozymes) has received significant attention for biosensing, biocatalysis, and nanomedical applications such as therapeutic treatments is developing. The functionality of metal nanoclusters (MNCs) as nanoenzymes is intriguing due to their better stability, biocompatibility, ease of fabrication technique, etc. These MNCs promote an intermediate state of molecules and metal nanoparticles (MNPs) and possess several intriguing properties. The high surface area to volume ratio makes them advantageous catalytically active materials and useful for enzyme activities. Yan et al first demonstrated Fe 3 O 4 nanoparticles (NPs) as artificial nanozymes that exhibit intrinsic peroxidase-like activity . They also discovered that this enzymatic activity of Fe 3 O 4 NPs is accelerated by a single amino acid, i.e.…”
Section: Introductionmentioning
confidence: 99%